Pluralisme Agama di Indonesia dalam Pandangan Abd. A’la - Atik Machmudah (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2019)
Abstract: This article discusses the views of Abd. A'la on religious pluralism. The problems discussed to obtain data in writing this thesis are: 1). What is the biography of Abd A'la, 2). What is Abd A'la's view of religious pluralism in Indonesia, and 3). How is the effort to realize the value of religious pluralism based on Pancasila values. In writing this article the research method used is the historical research method using four stages, including: heuristics (source collection), verification (source criticism), interpretation (interpretation of sources) and historiography (history writing). The first approach used in this study is the historical approach. Both approaches are descriptive qualitative. While the theory used is the structural functional theory put forward by Talcott Parsons. The results of this research article are (1). Abd A'la is a historical intellectual figure at UIN Sunan Ampel Surabaya who is an expert in the history of the development of Islamic thought. He is the son of Mr. KH. Ahmad Bashir and Nyai Hj. Umamah Makkiyah, who was born in Madura on September 5, 1957. Many written works have been published, including books discussing pluralism. (2). In his view, the values ​​of religious pluralism in Indonesia have been well instilled by Indonesian society. (3). The occurrence of various conflicts that occurred in Indonesia has a negative impact that will divide the unity and integrity of the Indonesian nation. Keywords: pluralism, religion, differences